PENDAMPINGAN KETERAMPILAN PARENTING DALAM MENYEMAI KASIH SAYANG PADA PROGRAM PENDIDIKAN NONFORMAL DI INDRAGIRI HULU - Afrida Yanis; Juni Erpida Nasution; Novri Susanti Suparman (LP2M IAIN Sultan Amai Gorontalo, 2024)
The Community Partnership Program (PKM) in Indragiri Hulu, Riau, aims to enhance parenting skills based on compassion through non-formal education programs. The primary issue addressed is the low quality of traditional parenting practices, which often lack emphasis on communication and emotional closeness between parents and children. This program aims to equip parents with effective parenting skills, foster harmonious family relationships, and support children’s optimal development. The method employed is a community-based training approach, including mentoring sessions and group discussions. The formation of Parenting Support Groups (PSG) is one of the key innovations, providing a platform for parents to share experiences and mutual support. Additionally, the use of digital technology enables sustained access to parenting information. The program successfully transformed traditional parenting patterns into practices rooted in compassion and emotional attentiveness. Parents gained a better understanding of their children’s needs, resulting in closer relationships and a supportive family environment. PSG strengthened social networks, enhanced community solidarity, and promoted the sustainability of positive parenting practices. This program significantly impacts the creation of harmonious families and communities more attentive to children's well-being. Through community-based and technology-supported approaches, the program contributes to sustainable social change and improved quality of life for the community.